AN OVERVIEW OF GREEN BANKING PRACTICES IN UZBEKISTAN - Gulomkodirova Mamura Saydumarxon qizi (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The research draws on existing literature on green banking practices, as well as case studies of banks in Uzbekistan. This approach allowed for a thorough and comprehensive understanding of the topic. The main purpose of this paper is to provide an overview of green banking practices in Uzbekistan, with a focus on mobile banking, online banking, green financing, and guidelines for green banking practices. This paper will also explore the role of green banking in promoting CSR (Corporate Social Responsibility) and will discuss the importance of green banking in Uzbekistan, and the challenges that need to be overcome in order to implement it effectively. The literature review revealed a number of important findings, including the lack of standardized definitions for green banking practices, the challenges faced by banks in implementing these practices, and the benefits that can be gained by doing so. These findings will be further explored in the main body of the paper.